The Portrayal of Masculinity in to Catch a Prince by Gillian Mcknight - Adisty Tyaputri Ariani (Passage, 2015)
This study entitled ‘The Portrayal of Masculinity in To Catch a Prince by Gillian McKnight’ aims to find the types of masculinity portrayed in the novel and their meanings. It applies a context-oriented approach and employs the textual analysis technique to answer the research questions. The data are analyzed using Rende’s chick lit theory (2008) and Harris’s theory of masculinity male messages (2005). The findings show that masculinity is portrayed through five types: the perfect man, the controlling man, the lover, the forbearing man, and the nature lover. It can be assumed that traditional masculinity which asserts strong, independent, achieving, hardworking, heterosexual, tough, aggressive, unemotional, physical, competitive, and forceful is still prevailed. In this text, it implies that it is related to the masculinity of fairy tales which are known to champion masculinity. The study implies that fairy tales underpin chick litKeywords: Chick lit, Harris, literature, masculinity, traditional